Predictors of poor outcomes after significant chest trauma in multiply injured patients: a retrospective analysis from the German Trauma Registry (Trauma Register DGU®) - Huber, Stephan (Scand J Trauma Resusc Emerg Med, 2014)
BACKGROUND: Blunt thoracic trauma is one of the critical injury mechanisms in multiply injured trauma victims. Although these patients present a plethora of potential structural damages to vital organs, it remains debated which injuries actually influence outcome and thereby should be addressed initially. Hence, the aim of this study was to identify the influence of critical structural damages on mortality. METHODS: All patients in the database of the TraumaRegister DGU® (TR-DGU) from 2002–2011 with AIS Chest ≥ 2, blunt trauma, age of 16 or older and an ISS ≥ 16 were analyzed. Outcome parameters were in-hospital mortality as well as ventilation time in patients surviving the initial 14 days after trauma. RESULTS: 22613 Patients were included (mean ISS 30.5 ± 12.6; 74.7% male; Mean Age 46.1 ± 197 years; mortality 17.5%; mean duration of ventilation 7.3 ± 11.5; mean ICU stay 11.7 ± 14.1 days). Only a limited number of specific injuries had a significant impact on survival. Major thoracic vessel injuries (AIS ≥5), bilateral lung contusion, bilateral flail chest, structural heart injury (AIS ≥3) significantly influence mortality in study patients. Several extrathoracic factors (age, blood transfusion, systolic blood pressure and extrathoracic severe injuries) were also predictive of increased mortality. Most injuries of the thoracic wall had no or only a moderate effect on the duration of ventilation. Injuries to the lung (laceration, contusion or pneumothoraces) had a moderate prolonging effect. Cardiac injuries and severe injuries to the thoracic vessels induced a substantially prolonged ventilation interval. CONCLUSIONS: We demonstrate quantitatively the influence of specific structural damages of the chest on critical outcome parameters. While most injuries of the chest wall have no or only limited impact in the study collective, injuries to the lung overall show adverse outcome. Injuries to the heart or thoracic vessels have a devastating prognosis following blunt chest trauma.